Spontaneous Cardiac Calcinosis in BALB/cByJ Mice - Glass, Aaron M (American Association for Laboratory Animal Science, 2013)
BALB/c mice are predisposed to dystrophic cardiac calcinosis—the mineralization of cardiac tissues, especially the right ventricular epicardium. In previous reports, the disease appeared in aged animals and had an unknown etiology. In the current study, we report a substrain of BALB/c mice (BALB/cByJ) that develops disease early and with high frequency. Here we analyzed hearts grossly to identify the presence and measure the severity of disease and to compare BALB/c substrains. Histologic analysis and fluorescent and immunofluorescent microscopy were used to characterize the calcinotic lesions. BALB/cByJ mice exhibited more frequent and severe calcium deposition than did BALB/c mice of other substrains (90% compared with 3% at 5 wk). At this age, lesions covered an average of 30% of the total ventricular surface area in BALB/cByJ mice, compared with less than 1% in other strains. In bone-marrow–chimeric mice, green fluorescent protein was used as a marker to show that the lesions contain an infiltration of cells of bone marrow origin. Lesion histology showed that calcium deposits were surrounded by fibrosis with interspersed immune cells. Lymphocytes, macrophages, and granulocytes were all present. Internalization of the gap-junction protein connexin 43 was observed in myocytes adjacent to lesions. In conclusion, BALB/cByJ mice exhibit more frequent and severe dystrophic cardiac calcinosis than do other BALB/c substrains. Our findings suggest that immune cells are actively recruited to lesions and that myocyte gap junctions are altered near lesions.